2021
DOI: 10.1002/pon.5616
|View full text |Cite
|
Sign up to set email alerts
|

Problem alcohol use among rural head and neck cancer patients at diagnosis: Associations with health‐related quality of life

Abstract: Objective Problem alcohol use in persons with head and neck cancer (HNC) is associated with poor outcomes, including survival. Some evidence suggests that individuals living in rural areas may be at greater risk of problem alcohol use. The present exploratory cross‐sectional study sought to examine problem alcohol use at diagnosis in a sample of HNC patients by rural versus urban status. Methods Self‐reported problem alcohol use as measured by the Short Michigan Alcoholism Screening Test (SMAST) was examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Therefore, even when offered as part of comprehensive cancer care, consideration should be given to the existence of treatment options close to the patient if specialty treatment referral is in order and/or alternative modes of delivery for those services that are not nearby. Recent studies have shown rural-residing patients with HNC may be more likely to report problem drinking behavior and, of those, many exhibit at least mild to moderate depressive symptomatology [13,43]. This suggests that behavioral health connections may be especially valuable for this important subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, even when offered as part of comprehensive cancer care, consideration should be given to the existence of treatment options close to the patient if specialty treatment referral is in order and/or alternative modes of delivery for those services that are not nearby. Recent studies have shown rural-residing patients with HNC may be more likely to report problem drinking behavior and, of those, many exhibit at least mild to moderate depressive symptomatology [13,43]. This suggests that behavioral health connections may be especially valuable for this important subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modality was classified as surgery/chemotherapy/radiotherapy only, combination (i.e., multimodal), or other/unknown. Depressive symptoms were assessed using the Beck Depression Inventory (BDI), a widely utilized and well validated measure of depressive symptomatology with scores ranging from 0 to 63, which has been used in previous studies of HNC [11,13].…”
Section: Tobacco Use and Other Key Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were published on risk factors and prevalence. [66][67][68][69] A study of 1990 data by Schreinemachers et al 69 found a lower rate of oral cavity and larynx cancers in agricultural Minnesota, while newer studies 66,68 have demonstrated increasing rural incidence of head and neck cancers. Finally, 2 studies evaluated disparities in hospital outcomes of patients with head and neck cancer, with 1 study identifying lower costs and shorter length of stay in rural hospitals 70 but another study noting increased mortality for hospitalized patients with head and neck cancer.…”
Section: Head and Neck Cancermentioning
confidence: 99%